2020
DOI: 10.1111/eva.13025
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization reduces gene flow but not genetic diversity of stream salamander populations in the New York City metropolitan area

Abstract: Natural landscape heterogeneity and barriers resulting from urbanization can reduce genetic connectivity between populations. The evolutionary, demographic, and ecological effects of reduced connectivity may lead to population isolation and ultimately extinction. Alteration to the terrestrial and aquatic environment caused by urban influence can affect gene flow, specifically for stream salamanders who depend on both landscapes for survival and reproduction. To examine how urbanization affects a relatively com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 182 publications
(200 reference statements)
1
28
0
Order By: Relevance
“…S2). Other studies with data not included in our synthesis have also found that genetic diversity did not decrease with urbanization in wood frogs (Furman, Scheffers, Taylor, Davis, & Paszkowski, 2016), fire salamanders (Lourenço, Álvarez, Wang, & Velo-Antón, 2017), and northern two-lined salamanders (Fusco, Pehek, & Munshi-South, 2020). Abundance in a species of frog related to the spring peeper, the boreal chorus frog ( P. maculata ), had a positive relationship with urbanization, which may be attributed to its preference for open habitats, or potential breeding habitats near roads (Browne, Paszkowski, Foote, Moenting, & Boss, 2009).…”
Section: Discussionmentioning
confidence: 62%
“…S2). Other studies with data not included in our synthesis have also found that genetic diversity did not decrease with urbanization in wood frogs (Furman, Scheffers, Taylor, Davis, & Paszkowski, 2016), fire salamanders (Lourenço, Álvarez, Wang, & Velo-Antón, 2017), and northern two-lined salamanders (Fusco, Pehek, & Munshi-South, 2020). Abundance in a species of frog related to the spring peeper, the boreal chorus frog ( P. maculata ), had a positive relationship with urbanization, which may be attributed to its preference for open habitats, or potential breeding habitats near roads (Browne, Paszkowski, Foote, Moenting, & Boss, 2009).…”
Section: Discussionmentioning
confidence: 62%
“…Assessing differences in phenotypic variation between urban and non-urban populations of less mobile species will be important to evaluate how biological traits (e.g., dispersal ability) determine the evolutionary impact of urban ecological conditions. Previous work in mammal and amphibian species with lower dispersal ability than birds suggests a comparable level of (genetic) variation between urban and non-urban habitats (Fusco et al . 2021; Richardson et al .…”
Section: Discussionmentioning
confidence: 99%
“…In the first study, Fusco et al. (2020) examined Northern two‐lined salamanders ( Eurycea bislineata ) which are native to the New York City metropolitan area and live in urban, suburban, and rural stream environments. Fusco et al.…”
Section: The Special Issuementioning
confidence: 99%
“…Fusco et al. (2020) found that populations experience reduced gene flow in urban areas, and this reduction was correlated with buildings, roadways, and residential housing. Yet, despite this disturbance and reduced gene flow due to urban development, all populations maintained similar levels of genetic diversity.…”
Section: The Special Issuementioning
confidence: 99%
See 1 more Smart Citation